Wall temperature and system mass effects in a reciprocating gas spring - Taleb,AI; Sapin,P; Barfuss,C; White,AJ; Fabris,D; Markides,CN (2016)
Reciprocating-piston devices can be used as high-efficiency compressors or expanders in small-scale Rankine cycle engines for power generation or in energy storage systems. The thermodynamic performance of piston-cylinder devices is adversely affected by the unsteady heat transfer between the compressed/expanded gas and the surrounding cylinder walls. Gas springs are an excellent model for the study of these losses because they exhibit the same complex heat transfer due to periodic pressure oscillations while avoiding the complexities of gas intake or exhaust. In this paper, results from CFD simulations of gas springs are compared to experimental data obtained in a piston-cylinder crankshaft-driven gas spring that experiences mass leakage. The temperature of the walls of the gas spring and the system mass are not known precisely in the experiments and are important parameters that determine the operation and performance of the system. The aim of this paper is to use complementary experimental and computational data in order to study the effects of these two parameters. Initial (mass) and boundary (wall temperature) conditions of the CFD are varied to match experimental measurements. It is found that the mass of the system has little influence on the temperature while an increase leads to a higher mean cyclic pressure without affecting the pressure ratio. In other words, the mass in a perfectly sealed gas spring only influences the operational pressure but not the performance of the system.